Effect of the PPARG2 Pro12Ala Polymorphism on Associations of Physical Activity and Sedentary Time with Markers of Insulin Sensitivity in Those with an Elevated Risk of Type 2 Diabetes. - Thomas Yates; Melanie J Davies; Joseph Henson; Charlotte Edwardson; David Webb; Danielle H Bodicoat; M'Balu Webb; Philip Howard; Jackie A Cooper; Steve E Humphries; Kamlesh Khunti; Philippa Talmud (PLoS ONE)
Background Peroxisome proliferator-activated receptor gamma (PPARγ) is an important regulator of metabolic health and a common polymorphism in the PPAR-γ2 gene (PPARG2) may modify associations between lifestyle behaviour and health. Objective To investigate whether the PPARG2 Pro12Ala genotype modifies the associations of sedentary behaviour and moderate-to-vigorous intensity physical activity (MVPA) with common measures of insulin sensitivity. Methods Participants with a high risk of impaired glucose regulation were recruited, United Kingdom, 2010-2011. Sedentary and MVPA time were objectively measured using accelerometers. Fasting and 2-hour post-challenge insulin and glucose were assessed; insulin sensitivity was calculated using Matsuda-ISI and HOMA-IS. DNA was extracted from whole blood. Linear regression examined associations of sedentary time and MVPA with insulin sensitivity and examined interactions by PPARG2 Pro12Ala genotype. Results 541 subjects were included (average age = 65 years, female = 33%); 18% carried the Ala12 allele. Both sedentary time and MVPA were strongly associated with HOMA-IS and Matsuda-ISI after adjustment for age, sex, ethnicity, medication, smoking status and accelerometer wear time. After further adjustment for each other and BMI, only associations with Matsuda-ISI were maintained. Every 30 minute difference in sedentary time was inversely associated with a 4% (0, 8%; p = 0.043) difference in Matsuda-ISI, whereas every 30 minutes in MVPA was positively associated with a 13% (0, 26%; p = 0.048) difference. The association of MVPA with Matsuda-ISI was modified by genotype (p = 0.005) and only maintained in Ala12 allele carriers. Conversely, sedentary time was not modified by genotype and remained inversely associated with insulin sensitivity in Pro12 allele homozygotes. Conclusion The association of MVPA with Matsuda-ISI was modified by PPARG2 Pro12Ala genotype with significant associations only observed in the 18% of the population who carried the Ala12 allele, whereas associations with sedentary time were unaffected.